A metodologia das ciências sociais sob uma perspectiva integradora : uma nova abordagem das vertentes qualitativas e quantitativas - Daise Menezes Guimarães (2006)
The prevalence of the dichotomous vision of Qualitative and Quantitative methodological tendencies of Social Sciences has brought about prejudices and stereotypes in relation to one or another methodology. Some contributions are presented herein for the development of investigations that surpass this dichotomous vison that does not satisfy researchers and investigators, as it limits the range of analytical options to only two possibilities. In such a context, the methodological integration presents itself as a viable and promising alternative, since it makes possible the approach of the social phenomenon taking into consideration its multiple aspects. In this dissertation, the methodological dichotomy configuration is analysed from the origin of Social Sciences on, appraising the elements which have contributed for the development of methodological antagonisms. Thereafter, a discussion toward the deconstruction of such a vision is developed, in order to present the arguments showing that the methodological integration is a viable and promising option in this scientific field. These arguments arise from the discussion of some researches that put into practice this form of investigative work.